Global Stability of Covid-19 Disease Free Based on Sivrs Model - Ratna Widayati (Department of Mathematics, Hasanuddin University, 2023)
This study discusses the spread of the Covid-19 disease by including new variant variables. The model used by SIVRS assumes there are deaths caused by Covid-19 and the new variant Covid-19. In addition, individuals who have been infected with the new variant of Covid-19 can recover. Based on the model, disease-free equilibrium points and endemic equilibrium points are obtained. The analysis was carried out around the disease-free equilibrium point and the result was that the global asymptotically stable disease-free equilibrium point with the condition R0<1. Furthermore, a simulation was carried out with the Maple 18.